2000
DOI: 10.1097/00004872-200018080-00021
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid, diuretic treatment and risk of cardiovascular events in the Systolic Hypertension in the Elderly Program (SHEP)

Abstract: Serum uric acid independently predicts cardiovascular events in older persons with isolated systolic hypertension. Monitoring serum uric acid change during diuretic treatment may help to identify patients who will most benefit from treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
2
16

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(195 citation statements)
references
References 24 publications
4
173
2
16
Order By: Relevance
“…Previous epidemiologic studies have also shown that UA level was independently predictive for the development of CVD even after antihypertensive treatment. 7,8,35,36 Furthermore, in the Systolic Hypertension in the Elderly Program trial, a subanalysis showed that the cardioprotection by diuretics was lost in those treated patients in whom UA levels increased. 36 One notable result of this study is that, in the group with higher LVMI, the risk of CVD became higher with increasing UA level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiologic studies have also shown that UA level was independently predictive for the development of CVD even after antihypertensive treatment. 7,8,35,36 Furthermore, in the Systolic Hypertension in the Elderly Program trial, a subanalysis showed that the cardioprotection by diuretics was lost in those treated patients in whom UA levels increased. 36 One notable result of this study is that, in the group with higher LVMI, the risk of CVD became higher with increasing UA level.…”
Section: Discussionmentioning
confidence: 99%
“…24 In the present study, we also found that DcT had a significant positive relationship with age (male: rϭ0. 36 …”
Section: Association Between Ua and Lvmimentioning
confidence: 99%
“…The reason why diuretics do not seem protect renal function may be due to diuretic-induced hyperuricemia, which could counteract some of the beneficial effects of diuretics in these latter conditions. While this has not been studied directly, it is interesting that in the Systolic Hypertension in the Elderly Program (SHEP) trial, the use of diuretics resulted in a significant reduction of cardiovascular events, but this protection was largely prevented in those patents whose uric acid levels increased [22]. However, we need randomized clinical trials to address the causal role of hyperuricemia in renal and cardiovascular disease.…”
Section: Clinical Evidence For Hyperuricemia In Renal Diseasementioning
confidence: 99%
“…Raised serum uric acid concentrations are associated with increased risk of stroke in high risk patient groups like hypertension, cardiovascular diseases and diabetes mellitus (27) . It is unclear whether high uric acid concentration promotes or protects against the development of ischemic stroke or simply act as a passive marker of increased risk.…”
Section: Discussionmentioning
confidence: 99%